Premenstrual Syndrome Levels and Eating Attitudes Among University Students - Bahadur, Ceyda; Ergen, Dilara; Yildiz, Nesibe; Dokumacioglu, Eda (Makara Journal of Health Research, 2023)
Background: Premenstrual syndrome (PMS) is the combination of physical, behavioral, and psychological symptoms that characterize the week leading up to menstruation, and it can last for a few days. This study aimed to investigate irregular PMS, eating attitude behavior, and body mass index values among university students. Methods: The study sample consisted of 140 Artvin Coruh University students studying Nutrition and Dietetics. The study includes questions from three separate sections. The first section contains a sociodemographic characteristic form, the second section consists of the Premenstrual Syndrome Scale (PMSS), and the third section includes the 26-item Eating Attitude Test (EAT-26). Results: In this study, the mean total score for PMSS was 135 ± 38.3, and the mean total score for EAT-26 was 17.0 ± 10.8. Individuals with irregular sleep patterns experienced more severe PMS (p < 0.01) and a shorter daily sleep duration (p < 0.05). Conclusions: High percentages of nutrition and dietetics students in our study experienced PMS, and the incidence of eating disorders was low. The relationship between PMS and EAT-26 must be understood for the health and well-being of university students.